Pengaruh Komunikasi Interpersonal terhadap Kinerja Karyawan (Studi Kasus pada Record Center Kantor DPRD Provinsi Sumatera Selatan) - Salsabila, Klara (Jurnal Flight Attendant, 2025)
Communication is a behavior that allows humans to receive and convey information according to needs. Interpersonal communication is part of many of communication because of its spontaneous nature and immediate feedback. Interpersonal communication can be done both face-to-face and through the media, and both often unconsciously affect various aspects of life, including in a professional setting, Within the framework of an organization, such as in the workplace, interpersonal communication requires a process to achieve the desired performance. Effective interpersonal communication can convey information quickly and provide clearer ideas, which is very important in a work environment. This Research seeks to examine the impact of interpersonal communication on employee effectiveness at the Record Center of the South Sumatra Provincial Parliament Office. The research method used is qualitative descriptive, which explains The impact of interpersonal communication employee effectiveness in the unit. The outcome of the study show that interpersonal communication plays a crucial a role in improving work performance, as it allows for effective information exchange, builds good working relationships, and creates a harmonious work environment. Through good communication, employees can more easily understand tasks, receive feedback, and resolve conflicts quickly, which ultimately increases individual and team motivation, collaboration, and productivity.